Studi Teologis Kepemimpinan Nehemia Berdasarkan Kitab Nehemia - Perangin Angin, Yakub Hendrawan; Arifianto, Yonatan Alex; Yeniretnowati, Tri Astuti (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2022)
This research shows leadership practices that have been thousands of years old and have succeeded brilliantly, but the principles contained in them still apply today and even in the era of the future. The uniqueness and richness of the leadership performed by Nehemiah as recorded in the Old Testament proves that the principles of reliable leadership not only in the world of religious service but also in the world of work are applied. The method used in this article is a qualitative method of library research. The results of this study show that Nehemiah's excellent leadership principles and become a role model for Christian leadership in any field can be applied, at least there are eight leadership principles, namely: First, Leadership that focuses on God. Second, leadership that understands the organizational context. Third, leadership based on risk and information thinking. Fourth, leadership that implements a comprehensive strategy. Fifth, servant leadership. Sixth, Empowering leadership with love and example. Seventh, effective and efficient leadership in managing resources. Eighth, leadership that conducts audits and complies with regulations and makes corrections.Abstrak Penelitian ini menunjukkan praktik kepemimpinan yang sudah berusia ribuan tahun dan berhasil dengan gemilang namun prinsip-prinsip yang terkandung di dalamnya masih terus berlaku di zaman ini bahkan zaman era ke depan. Keunikan dan kekayaan kepemimpinan yang dilakukan oleh Nehemia yang tercatat dalam Kitab Perjanjian Lama membuktikan kaidah-kaidah kepemimpinan yang handal bukan saja di dunia pelayanan keagamaan namun juga di dunia kerja diterapkan. Metode yang digunakan dalam artikel ini adalah metode kualitatif riset pustaka. Hasil penelitian ini menunjukkan prinsip-prinsip kepemimpinan Nehemia yang prima dan menjadi role model kepemimpinan Kristen di area bidang apapun dapat diterapkan, paling tidak ada delapan prinsip kepemimpinan, yaitu: Pertama, Kepemimpinan yang fokus pada Allah. Kedua, Kepemimpinan yang memahami konteks organisasi. Ketiga, Kepemimpinan yang berbasis berpikir risiko dan informasi. Keempat, Kepemimpinan yang menerapkan strategi komprehensif. Kelima, Kepemimpinan yang melayani. Keenam, Kepemimpinan yang memberdayaan dengan kasih dan teladan. Ketujuh, Kepemimpinan yang efektif dan efisien mengelola sumber daya. Kedelapan, Kepemimpinan yang melakukan audit dan patuh peraturan serta melakukan korektif.